Inclusive Regional Development: Implementation of the Child-Friendly Regency Policy in Bogor Regency - Aryani, Nanda Dita; Silitonga, Mala Sondang (International Journal of Economics Development Research (IJEDR), 2025)
This study explores the implementation of the Child-Friendly Regency/City (KLA) policy in Bogor Regency, specifically focusing on Cluster III: Basic Health and Welfare, as part of efforts to promote inclusive regional development. The research is motivated by the high infant mortality rate in Bogor Regency—the highest in West Java with 799 reported cases—and the region’s current "developing" status in the national KLA assessment. Employing a qualitative descriptive approach, data were collected through interviews, document analysis, and field observations. The findings reveal four key obstacles hindering effective policy implementation: (1) the absence of local regulations governing child-friendly childbirth services and health facilities; (2) limited infrastructure and transportation access to healthcare for remote communities; (3) low public awareness regarding the importance of national health insurance (BPJS) and inadequate dissemination of early childhood nutrition programs; and (4) an insufficient number of child-friendly health centers. To address these challenges, the study recommends four strategic interventions: establishing a legal framework through regional regulations for child-friendly health indicators, improving infrastructure and transportation access, enhancing community literacy on child nutrition and health services, and expediting the verification of child-friendly healthcare facilities. These measures are essential for fostering inclusive development and advancing child welfare in the region.